Synthesis of nanofluid, heat transfer and friction loss of nanofluid in different shaped heat exchanger tubes / Omar Fayez Almatar Abd Rabbuh - Omar Fayez Almatar , Abd Rabbuh (2019)
This thesis presents the impact of nanofluids on heat transfer and pressure drop utilizing different shaped heat exchanger tubes, which opens a new avenue in order to obtain the most effective higher energy transportation. To illustrate this aim, dispersing a nanoparticle in a host fluid to enhance the thermal conductivity of the resulted fluid has been considered for many applications than other traditional fluids as it has higher thermal conductivity than the conventional fluids. In this thesis, the turbulent heat transfer effectiveness of carbon based nanofluids has evaluated in a comprised of test section, cooling loop appliance, tank, piping, sensors and data logger. Graphene Nanoplatelets (GNP) was covalently functionalized with extractions of clove buds and dispersed in distilled water base fluid. At different concentrations, the results showed that the colloidal suspension has higher thermal conductivity than distilled water and the conductivity enhanced with the rising of concentrations. In the next section of this thesis, development of the stability of the Graphene Nanoplatelets (GNP) has been ensured by using Raman spectroscopy and the thermogravimetric analysis was conducted to address the issue of surface tension. These coolants compared with the traditional coolants like water and found the favorable characteristics such as high thermal conductivity. In the Last phase of the investigation of the performance of heat transfer, thermophysical properties and pressure drop of GNP-based water nanofluid in different configurations of heat exchanger tubes was conducted. Regarding the results of this investigation, there is a substantial improvement on the rate of heat transfer related with the loading of well-dispersed GNP in the base fluid. Heat transfer coefficient enhanced with the increase of concentrations of the nanoparticles in the fluid whereas the pressure loss enhancement was much less relevant to the gain in heat transfer. Thus, the graphene water based nanofluids could be a potential heat exchanging liquid.